The implications of E Schillebeeckx’s theology of liberation for anthropology and creation - Malan, D. J. (Verbum et ecclesia, 1993)
The theology of Edward Schillebeeckx has direct relevance for the situation of violence in South Africa. Anthropology and creation are closely linked in his theology through Christology. Christology is "concentrated creation". It underscores the grace of God as well as the responsibility of man. The negative contrast experiences of humanity calls for decisive praxis. Praxis is the precursor of theology and the function of theology is to as certain whether the praxis of the church is secundam scripturas.